Incompressible limit of the Navier—Stokes model with a growth term. (November 2017) - Vauchelet, Nicolas; Zatorska, Ewelina
Abstract: Starting from isentropic compressible Navier–Stokes equations with growth term in the continuity equation, we rigorously justify that performing an incompressible limit one arrives to the two-phase free boundary fluid system.